Disrupting Supply Chains and Their Resilience: A Literature Review - Joanna DYCZKOWSKA; Marcin OLKIEWICZ (Communications of International Proceedings, 2023)
The article undertakes the task of sorting out the many aspects of supply chain disruption and resilience reflected in the keywords listed below, which have already entered the canons of supply chain vocabulary.. The purpose of this article is to identify supply chain interruptions, analyze and evaluate supply chain changes in today's global economy that occur for SCM adaptation. The study is of a theoretical-empirical type. Research methods used for the purpose of this work include: literature analysis of the subject. The research question is as follows: To what extent is there adaptability vs. resilience when supply chains are disrupted? The effects of SCM adaptation to changes in the environment are related to flexibility, sensitivity and resilience. Increasing resilience has now become an extremely important issue for strategic supply chain management. It must be based on analysis of the external and internal environment and SC monitoring.
Keywords: supply chain; disrupting; risks; resilience; CoVID-19 pandemic